Combined bilateral asymmetric hip dislocation and anterior shoulder dislocation - Uslu, Mustafa (Second Affiliated Hospital of Zhejiang University School of Medicine, 2012)
BACKGROUND: Traumatic bilateral hip dislocation is a rare condition. Anterior shoulder dislocation combined with this condition is even a rare occurrence. A 57-year-old man had bilateral asymmetric hip dislocation with a posterior wall fracture of the left acetabulum associated with right shoulder anterior dislocation caused by falling down from a cherry tree. Traumatic hip dislocation and anterior shoulder dislocation represent a true orthopedic emergency. METHODS: Closed reduction was performed immediately for three of the dislocated joints. Posterior wall fracture of the left acetabulum was treated with open reduction and internal fixation by screws. Because of the severity of associated complications like aseptic necrosis or posttraumatic osteoarthritis, efforts were made to ensure prompt diagnosis, therapy and prognosis. RESULTS: The patient was successfully treated by open reduction and internal fixation of the left acetabulum, and discharged from the hospital. CONCLUSION: Traumatic asymmetric hip dislocation and anterior shoulder dislocation are an orthopedic emergency and early diagnosis with immediate reduction of the dislocation is the key determinants of excellent result of treatment.